Divergent synthesis of oxepino-phthalides and [5,5]-oxaspirolactones through [2+2+2]- and [2+3]-annulation of alkynyl alcohols with a-ynone-esters - Kambale, Digambar A.; Borade, Balasaheb R.; Vinodkumar, Ramavath; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Unmasking the synthetic potential of alkyne functional group of alkynyl alcohols as surrogates of carbonyl compounds, herein we present the first Bronsted acid (TfOH)-catalyzed [2 + 2 + 2]-annulation of 4-pentyn-1-ols (possessing terminal alkyne) with a-ynone-esters to access tricyclic tetrahydro-oxepino-phthalides. Besides, an unprecedented synthesis of a-acetoaryl or a-alkynyl [5,5]-oxaspirolactones has been demonstrated by employing 4-pentyn-1-ols (possessing an internal alkyne) as an annulation partner, which proceeds through a divergent [2 + 3]-annulation pathway.